HUBUNGAN KONTROL DIRI DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA KEPERAWATAN - Devayanti, Putu Veren; Damayanti S., Made Rini; Suindrayasa, I Made (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022DO - 10.24843/coping.2022.v10.i03.p02, 2022)
Nursing students are expected to have good self-control skills because they are related to their future work as nurses. Students who are not able to control themselves well during the educational process will tend to do academic procrastination. Academic procrastination will have more negative impacts on students which can affect academic success. This study aimed to determine the relationship between self-control and academic procrastination in Nursing Students, Faculty of Medicine, Udayana University. The method used in this research is descriptive correlation with cross sectional design. The number of samples in this study were 164 students who were selected using a stratified random sampling technique. Spearman Rank was used to analyzed the data. Most of the respondents in this study had low self-control 57,9%) and moderate levels of academic procrastination (48,8%). The results of this study obtained p value of 0,000 (p ? 0,05). The correlation coefficient value obtained at -0,623 showing negative and strong correlation. These results indicate that there is a significant relationship between self-control and academic procrastination in nursing students, Faculty of Medicine, Udayana University.